Youth as a political subject: liminality and political agency - Campos, Ricardo (2024)
The literature on the articulation between youth and politics frequently oscillates between pessimistic visions, which point to the little participation and disinterest shown by young people or, on the contrary, by more optimistic visions, which highlight the vigor of more diffuse and extra-institutional forms of participation. In fact, since we are dealing with a vast and heterogeneous age category, marked by very distinct sociocultural conditions, both visions certainly portray juvenile realities. They are not, therefore, absolutely antagonistic perspectives. In this article we seek to discuss the issues of the articulation between youth and politics from a conception of youth as a political subject, marked by a condition of liminality (and subalternity).